Sex and Age Differences in the Association Between Social Determinants of Health and Cardiovascular Health According to Household Income Among Mongolian Adults: Cross-Sectional Study - Sun Young Shim; Hyeonkyeong Lee (JMIR Publications, 2023)
BackgroundAlthough social determinants of health (SDH) are an underlying cause of poor cardiovascular health (CVH), there is insufficient evidence for the association between SDH and CVH, which varies by sex and age among Mongolian adults. ObjectiveWe aimed to explore whether education, household income, and health insurance were associated with CVH according to sex and age among Mongolian adults. MethodsThe final sample included data on 5691 participants (male: n=2521. 44.3% and female: n=3170, 55.7%) aged 18-69 years from the 2019 World Health Organization STEPwise approach to noncommunicable disease risk-factor surveillance. CVH was measured using a modified version of Life's Simple 7 with 4 health behaviors (cigarette smoking, BMI, physical activity, and a healthy diet) and 3 biological factors (blood pressure, fasting glucose, and total cholesterol blood levels) and classified into poor, intermediate, and ideal levels as recommended by the American Heart Association. Multinomial logistic regression analyses examined the associations between SDH and CVH by monthly equivalized household income after adjusting for age, sex, work status, area, history of myocardial infarction or stroke, use of aspirin, and use of statin. Subgroup analyses were conducted to examine the associations between SDH and CVH based on sex and age, considering monthly equivalized household income as a key variable. ResultsUsing the ideal level of CVH as a reference, among those with the lowest household income, having less than 12 years of education, and not having health insurance were associated with poor CVH (education level: odds ratio [OR] 2.42, 95% CI 1.30-4.51; P=.006; health insurance: OR 2.17, 95% CI 1.13-4.18; P=.02). These associations were more profound among female individuals (education level: OR 2.99, 95% CI 1.35-6.63; P=.007; health insurance: OR 2.54, 95% CI 1.09-5.90; P=.03) and those aged 18-44 years (education level: OR 3.22, 95% CI 1.54-6.72; P=.002; health insurance: OR 2.03, 95% CI 0.98-4.18; P=.06). ConclusionsParticipants in the lowest household income group with lower educational levels and without health insurance were more likely to have poor CVH, and these results were more pronounced in female individuals and young adults. These findings suggest the need to develop strategies for CVH equity in Mongolian female individuals and young adults that consider income levels, education levels, and health insurance.